2004
DOI: 10.1063/1.1666977
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast polarization modulation induced by the “virtual excitation” of spin-polarized excitons in quantum wells: Application to all-optical switching

Abstract: The operation of an all-optical coherent polarization switch that makes use of spin-polarized virtual excitons in unstrained quantum wells is thoroughly investigated experimentally over a wide range of excitation intensities. The device is shown to exhibit a 415 fs switching time and a contrast ratio of >300:1 at ∼100 K in a thin (40 well) sample. The switching mechanisms are discussed in terms of the circular optical selection rules and the virtual excitation is studied by performing differential measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…1,2 In particular, optical switches based on saturable absorption have been extensively studied using various materials including semiconductor quantum dots, [3][4][5][6] quantum wells, [7][8][9][10] and organic materials. [11][12][13] Such switches require both large intensity modulation and ultrafast response, which has been a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In particular, optical switches based on saturable absorption have been extensively studied using various materials including semiconductor quantum dots, [3][4][5][6] quantum wells, [7][8][9][10] and organic materials. [11][12][13] Such switches require both large intensity modulation and ultrafast response, which has been a key issue.…”
Section: Introductionmentioning
confidence: 99%
“…A contrast ratio of -27:1 is achieved with a pulse-width-limited switching time of -575 fs. We find that the price paid for room temperature operation is a reduction in the contrast ratio and an increase in the number of residual carriers produced by the control pulse (in comparison to our original measurements [4] performed at -100 K); however, these carriers do not contribute substantially to the switch signal and should not significantly limit the repetition rate. The residual carriers loose their spin-polarization in -70 ps and are expected to recombine on the usual ns time scales.…”
Section: Conversely For T=±10 Ps [Figs 3(a) and 3(c)]mentioning
confidence: 69%
“…Accumulation of the carriers from pulse to pulse can ultimately limit the repetition rate of these devices. By contrast, we recently demonstrated a coherent polarization switch based on near-resonant excitation of spin-polarized virtual carriers (SPVC) that did not suffer from this same limitation [4]. We demonstrated that by taking advantage of the spin-dependent nonlinearities associated with a virtual population (that is, carriers that only exist while the control pulse is in the sample), femtosecond switching times and high contrast polarization modulation could be achieved without relying on fast spin relaxation times and without significant carrier accumulation.…”
mentioning
confidence: 89%
“…However, this group has been greatly expanded especially in recent years [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] . The most outstanding advantage of the QW-/QD-based switches is their ultra-high switching speed (response <10 ps).…”
Section: Quantum Optical Switchesmentioning
confidence: 99%
“…QW-based switches are usually operated based on inter-subband transition (ISBT) [27][28][29][30][31][32][33][34][35] or multiple QW intermixing (QWI) [36][37] . ISBT in semiconductor QWs possesses ultra-fast carrier relaxation (~1 ps) and high conduction-band offset at optical communication wavelengths, while QWI changes the effective transition energies of the electrons from the valence band to the conduction-band and shifts the position of the absorption edge.…”
Section: Quantum-well-based Switchesmentioning
confidence: 99%